2007
DOI: 10.1007/s10549-006-9273-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of polymorphisms in the promoters of matrix metalloproteinases 2 and 9 genes in breast cancer in South Brazil: preliminary results

Abstract: Recently, studies have been focused on single nucleotide polymorphisms (SNPs) in matrix metalloproteinases 2 (MMP-2 C-1306T) and 9 (MMP-9 C-1562T) promoter regions and its role as a risk factor for cancer development.Concerning to breast cancer and MMP-2 C-1306 T, two studies were reported so far. Zhou et al., in China, showed that T alelle carries have a diminished risk of cancer development [1]. However, no association was detected among genotypes, TNM stage and estrogen receptor (ER) status [1]. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 3 publications
1
33
7
Order By: Relevance
“…Notably, the -1306 T-allele frequency differs across ethnicities: Saudi (0.10), Chinese (0.12), Brazilian (0.18), Greek (0.18), Australian (0.24), Polish (0.24), Mexican (0.26), Swedish (0.26) (Grieu et al 2004;Zhou et al 2004;Lei et al 2007;Roehe et al 2007;Delgado-Enciso et al 2008;Beeghly-Fadiel et al 2009;Ledwoń et al 2013;Saeed et al 2013a;Zagouri et al 2013). However, when subgroup analysis by ethnicity was performed, we could only find that CC was associated with a significant increase in breast susceptibility among Latin-Americans in the dominant model and the association disappeared in other models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the -1306 T-allele frequency differs across ethnicities: Saudi (0.10), Chinese (0.12), Brazilian (0.18), Greek (0.18), Australian (0.24), Polish (0.24), Mexican (0.26), Swedish (0.26) (Grieu et al 2004;Zhou et al 2004;Lei et al 2007;Roehe et al 2007;Delgado-Enciso et al 2008;Beeghly-Fadiel et al 2009;Ledwoń et al 2013;Saeed et al 2013a;Zagouri et al 2013). However, when subgroup analysis by ethnicity was performed, we could only find that CC was associated with a significant increase in breast susceptibility among Latin-Americans in the dominant model and the association disappeared in other models.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 9 case-control studies were eligible Lei et al 2007;Roehe et al 2007;DelgadoEnciso et al 2008;Beeghly-Fadiel et al 2009;Ledwoń et al 2013;Saeed et al 2013a;Slattery et al 2013;Zagouri et al 2013). The flow chart of study selection is shown in Figure 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Chinese population showed that the -1306 CC genotype to double breast cancer probability (Zhou et al, 2004). Contrarily, Roehe et al (2007) reported that, no association between -1306 C>T polymorphism and breast cancer. Studies in a Swedish population reported that, no association was found between the MMP-2 promoter polymorphisms and CRC (Elander et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al studies show no effect of genotype on the increased risk of breast cancer and subsequent prognosis of survival for the T/T genotype [30]. Roehe and colleagues who have examined this polymorphism, in turn, report no dependence between the risk and clinicopathological features of breast cancer [41]. Beeghly-Fadiel and colleagues also studied other SNPs for MMP-9 gene, but their results do not indicate a relationship with the risk of breast cancer [52].…”
mentioning
confidence: 97%